2022
DOI: 10.3389/fnagi.2022.817889
|View full text |Cite
|
Sign up to set email alerts
|

Six Months of Piano Training in Healthy Elderly Stabilizes White Matter Microstructure in the Fornix, Compared to an Active Control Group

Abstract: While aging is characterized by neurodegeneration, musical training is associated with experience-driven brain plasticity and protection against age-related cognitive decline. However, evidence for the positive effects of musical training mostly comes from cross-sectional studies while randomized controlled trials with larger sample sizes are rare. The current study compares the influence of six months of piano training with music listening/musical culture lessons in 121 musically naïve healthy elderly individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 82 publications
1
12
0
Order By: Relevance
“…As reported in the first part of the paper, unimanual fine motor control especially evolved during the first half‐year of intervention. However, the 6‐month improvement was independent of M1 and is therefore likely to have other neuronal causes, probably not in single brain regions but instead in distributed neuronal networks (Bangert et al, 2006; Doyon et al, 2009), as we also have shown in Jünemann et al (submitted). As expected, M1 did not change alone in the PiPl group, but in concert with Put and Tha (and most certainly other neural structures) forming an effective and well‐connected network.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…As reported in the first part of the paper, unimanual fine motor control especially evolved during the first half‐year of intervention. However, the 6‐month improvement was independent of M1 and is therefore likely to have other neuronal causes, probably not in single brain regions but instead in distributed neuronal networks (Bangert et al, 2006; Doyon et al, 2009), as we also have shown in Jünemann et al (submitted). As expected, M1 did not change alone in the PiPl group, but in concert with Put and Tha (and most certainly other neural structures) forming an effective and well‐connected network.…”
Section: Discussionsupporting
confidence: 71%
“…Then, within each pair, participants were randomly assigned to either PiPl or MuCu. The equality of these factors in both groups was confirmed using chi‐squared and two‐sample independent t ‐tests (see Jünemann et al, 2022). The second half of the intervention period (i.e., months 6–12) was impacted by the COVID‐19 pandemic.…”
Section: Methodsmentioning
confidence: 86%
See 2 more Smart Citations
“…In a 2022 article published in Frontiers in Aging Neuroscience (6), researchers Jűnemann et al wrote about their work regarding the neurocognitive effects of 6 months of piano training on elderly individuals. In their introduction, the authors state that musical training is associated with brain plasticity and protection against age-related cognitive decline.…”
Section: Piano Training In Older Adults May Enhance Brain Functionmentioning
confidence: 99%